Relicthemisia, a new subgenus of the oil-collecting bee genus Centris Fabricius, 1804 with notes on distribution and host plants of C. xanthomelaena Moure & Castro, 2001 (Hymenoptera: Apidae) - Vivallo, Felipe; Zanella, Fernando César Vieira (European Journal of Taxonomy, 2021)
Centris xanthomelaena Moure & Castro, 2001 is a relict species, endemic to northeastern Brazil and broadly recorded within the semiarid region of Caatinga xerophilous open vegetation. It was originally included in the subgenus Paracentris Cameron, 1903 but posteriorly interpreted as remotely related to it or to the subgenus Centris s. str. Fabricius, 1804. In this paper it is proposed to recognize this species as the single member of the monotypic Relicthemisia, a new subgenus which belongs to the ‘Centris group’, one of the main internal lineages of the genus. The proposition of this new subgenus is based on both, morphological and molecular data which indicate its long history as a distinct lineage. Distribution records, floral hosts as well as photographs of both sexes of C. xanthomelaena are also provided.